Plant communities of melilotus officinalis (l.) in the suusamir valley and its beneficial properties. (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Research shows that, as a result of expeditionary trips to the Suusamyr Valley, we recorded plant communities of Melilotus officinalis (L.) in their natural habitat. The aim of this study is to provide a geobotanical and ecological characterization of the studied species, as well as its medicinal properties and potential for future use. The research results can be applied in pharmaceuticals, geobotany, and ecology to preserve biodiversity and as a raw material for medicinal use.
Keywords: essential oil crops, forb pastures, plant species, honey production, plant communities, medicinal plants